Kajian Teologis terhadap Konsep Perkawinan Ipar menurut Hukum Levirat di dalam Ulangan 25:5-6 - Heni Maria (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The term "levirate marriage" or brother-in-law marriage used in Deuteronomy is certainly not familiar to some people in modern times. The story of Ruth clearly shows that levirate marriage is actually based on Deuteronomy 25:5-6. This paper uses a systematic methodology by showing how the concept of levirate marriage is in Deuteronomy 25:5-6 and relates it to a theological understanding based on the Bible as a whole. The practice of levirate marriage in the text of Deuteronomy 25:5-6 had an important value in maintaining the family line and preventing the extinction of lineage in Jewish society at that time. However, the relevance of this practice to in-law marriage is still debated and is not used as a basis for in-law marriages in Judaism or other religions.